A new species of triadal coral snake of the genus Micrurus Wagler, 1824 (Serpentes: Elapidae) from northeastern Brazil - Pires, Matheus Godoy; Da Silva Jr., Nelson Jorge; Feitosa, Darlan Tavares; Prudente, Ana Lúcia Da Costa; Filho, Gentil Alves Pereira; Zaher, Hussam (Zootaxa, 2014)
The genus Micrurus comprises 123 currently recognized taxa (species and subspecies) that are traditionally arranged in four species groups diagnosable mainly by color pattern characteristics. Here, we describe a new species of triadal coral snake from northeastern Brazil. The new species is distinguished from other sympatric triadal congeners (M. lemniscatus carvalhoi, M. ibiboboca and M. brasiliensis) mainly by the entirely black parietals and by a suite of external characters and hemipenial morphology. The new species appears to be restricted to tropical ombrophilous lowland coastal forests of northeastern Brazil and all recently collected specimens are known to occur in small forest patches surrounded by periurban environment, which calls for an urgent evaluation on its conservation status.